Oncostatin M, an Underestimated Player in the Central Nervous System - Houben, Evelien; Hellings, Niels; Broux, Bieke (Frontiers in Immunology, 2019)
For a long time, the central nervous system (CNS) was believed to be an immune privileged organ. In the last decades, it became apparent that the immune system interacts with the CNS not only in pathological, but also in homeostatic situations. It is now clear that immune cells infiltrate the healthy CNS as part of immune surveillance and that immune cells communicate through cytokines with CNS resident cells. In pathological conditions, an enhanced infiltration of immune cells takes place to fight the pathogen. A well-known family of cytokines is the (IL)-6 cytokine family. All members are important for cell communication and cell signaling in the immune system. One of these members is Oncostatin M (OSM), for which the receptor is expressed on several cells of the CNS. However, the biological function of OSM in the CNS is not studied in detail. Here, we briefly describe the general aspects related to OSM biology, including signaling and receptor binding. Thereafter, the current understanding of OSM during CNS homeostasis and pathology is summarized.